Speaking Freely and Freedom of Speech: Why is Black Feminist Thought Left Out of Ontario University Sexual Violence Policies? - Ostridge, Lindsay (Atlantis)

(untitled) (Mount Saint Vincent University, 2020)
As of January 1, 2017, the Province of Ontario has required all post-secondary institutions to create and maintain a stand-alone sexual assault policy that includes clearly stated complaint and response procedures. This paper brings to bear the influence of Black feminist thought as an analytic tool and politic on the outcomes and omissions of the development of these policies. Analyzing the stand-alone sexual violence policy of the University of Ottawa as a case study, the author conducted a critical discourse analysis with an intersectional lens to determine if intersectionality influenced the policy creation. Findings reveal that policymakers conceptualize gender in a one-dimensional manner, without attention to intersections of sexualized violence with racism and other systems of oppression. A policy with an ill-defined focus on gender can result in a colorblind policy that suggests that the institution should treat all students the same, regardless of systemic disadvantages they might face on the basis of race, class, gender, sexual orientation, or ability. This avoidance can create barriers to reporting. Neoliberalism and the changing university culture are discussed.